3D printing in building and construction - Liu, Zhenbang (Nanyang Technological University, 2025)
Due to its advanced automation and design freedom, 3D concrete printing (3DCP) is gaining popularity in the building and construction (B&C) industry. Unlike traditional reinforced concrete (RC) structures, the fresh-state cementitious material is pumped and extruded layer by layer with no formwork support. Thus, comprehensive research is essential to evaluate the performance of 3D printing concrete at various stages: during printing, after concrete hardening, and when utilized as structural members. These stages correspond to three levels of investigations in this thesis: research on 3DCP buildability, examination of the mechanical properties of small-scale 3DCP units, and assessment of the structural behavior of large-scale 3DCP structural members, respectively. Correspondingly, four key themes were addressed as follows: